2014
DOI: 10.1111/hex.12295
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the relationship between science and society: Has there been a shift in attitudes to Patient and Public Involvement and Public Engagement in Science in the United Kingdom?

Abstract: BackgroundThe policy imperative to engage the public and patients in research can be seen as part of a wider shift in the research environment. This study addresses the question: Has there been a shift in attitudes to Patient and Public Involvement (PPI) and Public Engagement in Science (PES) amongst researchers?MethodsAttitudes to PPI and PES within a cluster of three NIHR supported Biomedical Research Centres were explored through in‐depth interviews with 19 researchers.ResultsParticipants distinguished PPI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 13 publications
2
123
1
Order By: Relevance
“…In 2015, the NIHR in the UK concluded that despite PPI being progressively adopted, there were “inconsistencies in practice and implementation” and cited negative attitudes of researchers as a major barrier. Consequently, PPI is still often relegated to the role of “thinker at the edges,” within a dominant positivist research paradigm that hinders the inclusion of “lived experiences” of health and illness.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the NIHR in the UK concluded that despite PPI being progressively adopted, there were “inconsistencies in practice and implementation” and cited negative attitudes of researchers as a major barrier. Consequently, PPI is still often relegated to the role of “thinker at the edges,” within a dominant positivist research paradigm that hinders the inclusion of “lived experiences” of health and illness.…”
Section: Discussionmentioning
confidence: 99%
“…14 There have been few studies of how researchers have responded to the pressure to move towards a more participatory model of knowledge production. 15 The privileging of scientific expertise over lay experience has been remarkably resilient, and it has been noted that researchers are reluctant to cede control over research. 16,17 Despite some interest in, and support for, PPI in theory, researchers may feel apprehensive and reluctant to change their practice, given other professional and institutional priorities.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…At the same time, there is limited evidence demonstrating that PPI has changed clinical research practices (Boaz et al . , Rise et al . ).…”
Section: Assetisation As Valuation Practicementioning
confidence: 99%